Denationalizing Science
VII, 303 p.
Keywords: Present trends indicate that in the years to come transnational science, whether basic or applied and involving persons, equipment or funding, will grow considerably. The main purpose of this volume is to try to understand the reasons for this denationalization of science, its historical contexts and its social forms. The Introduction to the volume sets out the socio-political, intellectual, and economic contexts for the nationalization and denationalization of the sciences, processes that have extended over four centuries. The articles examine the specific conditions that have given rise to the growth of transnational science in the 20th century. Among these are: the need for cognitive and technical standardization of scientific knowledge-products, pressure toward cost-sharing of large installations such as CERN, the voluntary and involuntary migration of scientists, and the global market for R&D products that has emerged at the end of the century. The volume raises many new questions for research by historians and sociologists of science and poses problems that are of concern both to scientists and science policy-makers.